mHealth Ecosystems and Social Networks in Healthcare - Lazakidou, Athina A.; Zimeras, Stelios; Iliopoulou, Dimitra; Koutsouris, Dionysios-Dimitrios (Annals of Information Systems, 2016)
Chapter 1: Emerging mHealth Ecosystems based on innovative technologies and services Vassileia Costarides, Kostas Giokas and Dimitris Koutsouris Chapter 2: Wearable Health Monitoring Systems: An overview of design research areas Amine Boulemtafes and Nadjib Badache Chapter 3: Citizen Engagement in the mHealth Ecosystem Using Mobiles and Wearable Devices Ioannis Kouris and Dimitrios Koutsouris Chapter 4: Innovative mHealth Ecosystems Dimitrios Tsoromokos, Zacharias Dermatis, Filippos Gozadinos and Athina Lazakidou Chapter 5: Mobile-Health Tool Use and Community Health Worker Performance in the Kenyan Context: A Comparison of Task-Technology Fit Perspectives Maradona C. Gatara Chapter 6: Design of Wearable Health Monitoring Systems: An overview of techniques and technologies< Nadjib Badache and Amine Boulemtafes Chapter 7: M-Health ecosystem based of a non-invasive commercial hemodynamic monitoring system used for heart failure patients, as portable point of care Petros Toumpaniaris, Kostas Giokas and Dimitris Koutsouris Chapter 8: How Knowledge Flows Through Social Networks and Communities of Practice in a Healthcare Project Maria Tsouri, Kleopatra Alamantariotou, Ourania Pediaditaki, Vikentia Harizopoulou and Georgia Kontosorou Chapter 9: A context-aware social networking platform built around the needs of elderly users: The Go-myLife experience Maria Haritou, Athanasios Anastasiou, Maria Schwarz-Woelzl, Teresa Holocher-Ertl, Michael Mulquin, Idoia Olalde, Ioannis Kouris and Dimitris Koutsouris Chapter 10: Cost effectiveness in healthcare using social networks Stelios Zimeras Chapter 11: Social Networks and Web-based Applications in the Healthcare Sector Athina Lazakidou Chapter 12: Knowledge Sharing in Health Innovation Projects: Experiential Learning from Collaborating in a Project-Based Working Group Focusing in Knowledge Transfer in Maternity Services Best Practice (COST Projects IS 0907) Kleopatra Alamantariotou and Katerina Nicolopoulou Chapter 13: Social Networks Medical Image Steganography using Sub-Fibonacci Sequences Nikolaos G. Aroukatos, Kostas Manes and Stelios Zimeras Chapter 14: Studying the information behavior of healthcare professionals in a Greek private clinic using social networks models P. Kostagiolas, Stelios Zimeras, G. Alexias and Z. Siskou.